A High Efficient Cross-Coupled Active Rectifier by Using High Speed Switching Comparators for Wireless Power Receiver - Syed Adil Ali Shah; Young-Gun Pu; Young-Joon Kim; Kang-Yoon Lee (IEEE Open Journal of Circuits and Systems, 2025)
This paper introduces a highly efficient cross-coupled active rectifier with fast switching comparators for wireless power transfer (WPT) system. Wireless power transfer technology is increasingly being utilized in various applications. In our proposed design an active diode switches are introduced at lower side of power MOSFET to minimize the switching delay in power transistors and also reduces reverse leakage current to boost power conversion efficiency. The active diode is constructed from high-speed comparators and CMOS power switches. A cross-coupled technique is applied to the high side PMOS power transistors, in order to minimizing power consumption and optimizing current management. This enhancement not only improves the power efficiency of the cross-coupled active rectifier but also prolongs battery life and boosts the overall Efficiency. The cross-coupled architecture of the proposed rectifier enables high-speed switching, which is necessary for its design. This allows for fast response times and efficient signal processing. The presented cross-coupled active rectifier is designed using $0.18~μ $ m CMOS technology. It delivers 2.77 W of output power using a $1~μ $ F capacitor with a 0.3A load current, and it achieves a power efficiency of 92.4%.